Structural modification of waste cooking oil methyl esters as cleaner plasticizer to substitute toxic dioctyl phthalate. (10th June 2018) - Zheng, Ting; Wu, Zhenyu; Xie, Qinglong; Fang, Jiaojiao; Hu, Yunchen; Lu, Meizhen; Xia, Fan; Nie, Yong; Ji, Jianbing
Abstract: Most of the plasticizers used during poly (vinyl chloride) processing are typically toxic petroleum-based phthalates. Furthermore, large amount of edible oils become waste all over the world, fortunately, waste cooking oils have the potential to be an economic alternative for synthesizing different biomaterials. This study aimed to synthesis an improved properties and cost competitiveness cleaner bio-plasticizer using waste cooking oil methyl esters as staring raw materials. In this paper, waste cooking oil methyl esters were structurally modified i.e., transesterification and epoxidation reaction, to prepare epoxide waste cooking oil 2-ethylhexyl esters. The in-situ epoxidation was mainly studied by response surface methodology, with optimum conditions: reaction time was 7 h, molar ratio of CC bonds/FA/H2 O2 was 1.00/0.35/2.41, and reaction temperature was 65.84 °C with a maximum relative percentage conversion to oxirane of 92%. Also, the plasticizing effectiveness of epoxide waste cooking oil 2-ethylhexyl esters to substitute toxic plasticizer dioctyl phthalate were studied. Results showed that the mechanical and thermal performance of PVC samples was significantly improved with partial substitutions, while the migration resistance was slightly decreased. Comparison with conventional epoxy compound highlighted that epoxide waste cooking oil 2-ethylhexyl esters had superior low temperature property, oxidation stability, and remarkably reduced the glass transition temperature of PVC. In conclusion, the prepared epoxide via structural modification from waste cooking oil methyl esters proved to be an effective alternative to dioctyl phthalate, replacing about 40% of the total plasticizer. This may lead to the eco-development of waste cooking oil materials, and makes the plasticizing process more environmentally friendly. Graphical abstract: Image 1 Highlights: An improved cleaner bio-plasticizer from waste cooking oil methyl esters. Optimization of important reaction parameters for bio-plasticizer production by RSM. Study of plasticizing effectiveness of synthesized bio-plasticizer to substitute toxic DOP. Comparison of novel bio-plasticizer with conventional epoxy plasticizers.